Knowledge and ethics in anthropology obligations and requirements - Josephides, Lisette (Bloomsbury, 2015)
This new collection of essays is inspired by the work of world-renowned anthropologist Marilyn Strathern and draws together the work of internationally recognized scholars, including Strathern herself, to examine a range of methodologies and approaches to the anthropology of knowledge. The book looks at the production of knowledge through a variety of different themes, all centered around the idea of the ethnographers' obligations and requirements, from the obligations of the anthropologist to connect with local culture and existing anthropological knowledge during research, to the need to draw conclusions and circulate what has been learned. Suitable for those approaching Strathern's ideas for the first time as well as experienced scholars, the book features a thorough introduction to the key concepts and terms used in Strathern's work. Taking up themes that are relevant for anthropology as a whole, particularly the topic of knowledge and the ethics of knowing others, as well as the notion of local in a global world, this will be key reading for upper-level undergraduates and graduates studying methods, knowledge production, gender and ethics